Mechanical Characterization and Simulation of Wood Textile Composites (WTC) supported by Digital Image Correlation (DIC) - Claudia Louise von Boyneburgk; Jan-Christoph Zarges; Detlef Kuhl; Hans-Peter Heim (Composites Part C: Open Access, 2023)
Wood Textile Composites (WTC) based on willow wood fabrics and polypropylene were produced using a hot compacting process in order to open up new and innovative areas of applications for wood. Due to their attractive and variable design, the WTCs are to be used in areas with a high visual impact, for example as a facade element. In tensile and 3-point bending tests, it was shown that the mechanical properties of WTC are strongly dependent on the heterogeneous structure of the composite. Both strength and elongation depend on the loading direction and show a classical fiber composite behavior despite the comparatively large dimension of the filaments. The properties of the material in the elastic range are of particular importance, which is why the tensile tests described in this work were supported by digital image correlation (DIC). They were simulated applying an orthotropic constitutive model and the finite element discretization of the test specimens.